Taguchi Grey relational analysis (GRA) based multi response optimization of flammability, comfort and mechanical properties in station suits - Hafsa Jamshaid; Awais Ahmad Khan; Rajesh Kumar Mishra; Naseer Ahmad; Vijay Chandan; Viktor Kolář; Miroslav Müller (Heliyon)
Fire fighters’ stations suits are expected to have adequate flame resistance for protection of the wearer. At the same time the comfort of wearing is essential to prevent fatigue and to maintain the efficiency during long working hours. Therefore, it is essential to balance these multi responses in a scientific manner. This study explores the multi-response optimization of fiber blend composition and knitted structures on the responses like flammability, comfort, and serviceability/mechanical properties, for the development of fire-resistant fabrics. Inherently fire-resistant (FR) fibers like meta-aramid Nomex, FR-Viscose, modacrylic (Protex) and carbon/Pyron fibers (Zoltek) were used in different blends to form yarns. Interlock derivative knitted structures like Cross Relief, Cross Miss and Vertical Tubular were developed. The results have been analyzed using Taguchi Grey relational analysis (GRA) for multi-response optimization. The analysis revealed that the sample with the blend of 70/30 % Protex/Nomex fiber and a Cross-relief structure ranked the best sample in terms of required performance. The percentage contribution of each factor was analyzed using ANOVA (α = 0.05) and visualized using a pie chart. While Factor B (Knitted Structure) demonstrated the highest variance contribution (42.3 %), it was not statistically significant based on the p-value and F-ratio from ANOVA results. The findings of this study are useful for designing flame-resistant uniforms/Station garment for firefighters without compromising wearing comfort so that the efficiency of the workers will not be compromised.